Imaging of intracellular-specific microRNA in tumor cells by symmetric exponential amplification-assisted fluorescence in situ hybridization. Issue 99 (27th November 2018) - Chen, Jun; Yin, Wen; Ma, Yingjun; Yang, Huihui; Zhang, Yanfei; Xu, Mengfei; Zheng, Xuling; Dai, Zong; Zou, Xiaoyong
Abstract : A symmetric exponential amplification-assisted fluorescence in situ hybridization (SEXPAR-FISH) strategy was reported for imaging intracellular-specific microRNAs. Abstract : We report a symmetric exponential amplification-assisted fluorescence in situ hybridization (SEXPAR-FISH) strategy for imaging intracellular-specific microRNAs (miRNAs) in cells. The strategy eliminates the risk of cell loss and miRNA leakage, and low-abundant intracellular miR-27a in cells can be imaged in only 2 h without compromising sensitivity and specificity.